2019
DOI: 10.1016/j.isci.2019.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Biocomputational Analyses and Experimental Validation Identify the Regulon Controlled by the Redox-Responsive Transcription Factor RpaB

Abstract: Summary Oxygenic photosynthesis requires the coordination of environmental stimuli with the regulation of transcription. The transcription factor RpaB is conserved from the simplest unicellular cyanobacteria to complex eukaryotic algae, representing more than 1 billion years of evolution. To predict the RpaB-controlled regulon in the cyanobacterium Synechocystis , we analyzed the positional distribution of binding sites together with high-resolution mapping data of transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 75 publications
(144 reference statements)
2
45
1
Order By: Relevance
“…The high-light responsive transcription factor RpaB (slr0947, regulator of phycobilisome association B) was upregulated in multiple mutants. The extensive regulon of RpaB includes likely repressor activity of linear electron transport at high light (e.g., subunits of PSII and Cyt-b 6 f), and activation activity of photoprotection and cyclic electron flow (e.g., ftsH and ssr2016) 26 . Other common upregulated genes are involved in electron transport (fed7), and include components of the NDH-1 complex (ndhD1, ndhD2) and carotenoid biosynthesis (crtQ and crtZ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The high-light responsive transcription factor RpaB (slr0947, regulator of phycobilisome association B) was upregulated in multiple mutants. The extensive regulon of RpaB includes likely repressor activity of linear electron transport at high light (e.g., subunits of PSII and Cyt-b 6 f), and activation activity of photoprotection and cyclic electron flow (e.g., ftsH and ssr2016) 26 . Other common upregulated genes are involved in electron transport (fed7), and include components of the NDH-1 complex (ndhD1, ndhD2) and carotenoid biosynthesis (crtQ and crtZ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription of the IsiA-encoding gene (isiA) is regulated by two transcription factors, RpaB (regulator of phycobilisome association B) and Fur (Ferric Uptake Regulator) 25 . RpaB controls the transcription of photosynthesis-associated genes in response to light 25 . Its binding motif, a high-light regulatory (HLR) sequence, is at upstream of many high-light-inducible genes including isiA ( Supplementary Fig.…”
Section: High Light Induces Isia Expression and Formation Of The Isiamentioning
confidence: 99%
“…Among the candidates for a trans-acting factor that binds the HLR1 element, RpaB, one of the response regulators of the two-component systems in Synechocystis PCC 6803, has been identified (Kappell and van Waasbergen, 2007). RpaB has been shown to bind to the HLR1 element on various high-light-responsive promoters by gel-shift analysis in Synechocystis PCC 6803 (Kadowaki et al, 2016;Kappel and van Waasbergen, 2007;Riediger et al, 2019;Seino et al, 2009;Takahashi et al, 2010) as well as in Synechococcus elongatus PCC 7942 (Kato et al, 2011;López-Redondo et al, 2010;Seki et al, 2007). Furthermore, a dynamic change in the RpaB binding pattern with Yasuda et al #5 target promoters under high-light-stress conditions has been observed in vivo by ChIP (Hanaoka et al, 2008) and ChAP (Kadowaki et al, 2016) analyses.…”
Section: Introductionmentioning
confidence: 93%